2020
DOI: 10.1017/dsj.2020.5
|View full text |Cite
|
Sign up to set email alerts
|

Research perspectives in ecodesign

Abstract: Ecodesign has gained significant traction in recent years ranging from academic research to business applications at a global scale. Initial emphasis on the environmental aspect of design has evolved to include economic and social aspects, with projects ranging from small-scale products to large-scale industrial systems. In this paper, the authors re-analyse 10 of their major ecodesign research projects of the past ten years to identify five categories of challenges and promising future directions for ecodesig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 106 publications
0
27
0
Order By: Relevance
“…In recent years, more and more industry case studies have emerged that relate in some way to design for sustainability within engineering design have been identified. Recent analysis of some of these across a number of industrial sectors identified five key issues that they address, resource use, lifespan, understanding use, integrating data and defining system boundaries (Kim et al 2020) illustrating that a largely incremental approach has been adopted to date. Whilst these only represent a subset of the issues that design for sustainability is concerned with it does show the direction of travel.…”
Section: The Engineering Design Response To Sustainable Developmentmentioning
confidence: 99%
“…In recent years, more and more industry case studies have emerged that relate in some way to design for sustainability within engineering design have been identified. Recent analysis of some of these across a number of industrial sectors identified five key issues that they address, resource use, lifespan, understanding use, integrating data and defining system boundaries (Kim et al 2020) illustrating that a largely incremental approach has been adopted to date. Whilst these only represent a subset of the issues that design for sustainability is concerned with it does show the direction of travel.…”
Section: The Engineering Design Response To Sustainable Developmentmentioning
confidence: 99%
“…Recent surveys identified over 600 unique eco-design tools or methods [7,8]. These eco-design, circular or sustainable design, and other "design for X" approaches have been developed and extensively reviewed by scholars [9][10][11][12][13][14][15][16][17][18]. They include a broad variety of practices, including multi-step methods, software tools, simple activities, broad mindsets, and checklists of goals; for inclusivity, this project refers to all of these practices as "sustainable design methods and tools" (SDMTs).…”
Section: Context and Motivationmentioning
confidence: 99%
“…Despite the proliferation of SDMTs through a wide variety of forms (guidelines, checklists, software, cards, mindsets, etc. ), their uptake by industry has been relatively low [11,[18][19][20].…”
Section: Context and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the past two decades, several literature reviews and research projects compiling knowledge on eco-design have been carried out. Some of the reviews focus on classifying the existing tools [9][10][11][12], while others are more focused on future trends of the tools [8,13]. However, literature is primarily concerned with eco-design in relation to product design and development.…”
Section: Introductionmentioning
confidence: 99%